Pharmacovigilance: A Pillar of Modern Drug Safety - Korade Payal B,; Khaire Rahul D,; Kathale Ankita A,; Sanke Lochani D,; Bhandare Tejashwini S,; Ghuge Samiksha K, (Asian Journal of Pharmaceutical Research and Development, 2025)
Pharmacovigilance (PV) Is A Pivotal Discipline In Clinical Research And Public Health, Focusing On The Detection, Assessment, Understanding, And Prevention Of Adverse Drug Reactions (Adrs). While PV Systems Are Well-Developed In High-Income Countries, They Remain Underdeveloped In Low- And Middle-Income Regions Such As India. This Review Highlights The Historical Evolution, Current Practices, And Future Prospects Of Pharmacovigilance, Emphasizing The Role Of Post-Marketing Surveillance, Risk Management, Patient Safety, And Vaccine Monitoring. It Also Explores Cutting-Edge Developments Including The Integration Of Big Data, Artificial Intelligence, And Pharmacogenomics To Enhance Personalized Medicine And Real-World Evidence Analysis. Despite These Advances, PV Faces Numerous Challenges, Including Under reporting, Poor Data Quality, Regulatory Barriers, Misinformation, Limited Integration Of Real-World Data, And Ethical Concerns Surrounding Data Privacy. The Document Advocates For Robust Policy Support, Capacity Building, Digital Infrastructure Development, And Global Collaboration To Address These Limitations And Ensure Drug Safety Across Diverse Populations.